Physical-Chemical Removal Of Ammonia, Iron And Zinc From Semi-Aerobic Landfill Leachate By Zeolite And Limestone - Lee, Ngan Siew (Universiti Sains Malaysia, 2005)
This study investigates the removal of ammonia, iron and zinc using zeolite and limestone as adsorbents. Literature review indicated that zeolite and limestone are capable of removing heavy metal cations through batch process. Therefore, batch experiments were carried out in this research to determine the efficiency removal of ammonia, iron and zinc in leachate taken from Pulau Burung Landfill Site. Shaking and settling times, shaking speed, the optimum mixture of zeolite and limestone were pre-determinated, respectively. Result show that the shaking and settling times were 1 hour, respectively. The optimum shaking speed was 350 rpm and the optimum mixture between zeolite and limestone was 15 mL of zeolite and 25 mL of limestone. Mixing the limestone with zeolite could reduce the cost of treatment. Adsorption isotherm at the optimum mixture was determined using Freundlich and Langmuir principle. The value of 1/n and Kf for iron was 0.5845 and 0.00062, respectively and was 1.4131 and 0.1683, respectively for zinc. The breakthrough time for iron and zinc was 4.28 and 4344.33 days, respectively at flow rate 460m3/day and 4.5 m3 column volume. Adsorption kinetics determination showed that it followed the pseudo second order chemical adsorption of R2 values for ammonia, iron and zinc was 0.9726, 0.9991 and 0.9958, respectively.